The secondary forest situation in Sri Lanka: a review - Perera, G.A.D. (2001)
Most forests in Sri Lanka are secondary, are mostly confined to the dry and intermediate zones of the country, and arise out of swidden agriculture. The majority of secondary forests which regenerate after swidden farming in the dry parts of Sri Lanka are grown from vegetative parts, that are from remaining roots and stumps. Secondary forests provide numerous products of importance to local people. They also help to bridge seasonal gaps in livelihoods. Secondary forests of Sri Lanka are being disturbed or transformed by intensive cultivation, fire, the implementation of development projects, the establishment of plantations and by the construction of houses by the local people. Secondary forests in the dry parts of Sri Lanka could be managed as conservation areas for timber production or for multiple uses. Regional climate, the ecology of secondary forests and anthropogenic pressures need to be considered when selecting suitable management options for a given site. Most of the secondary forests are heavily degraded and need to be rehabilitated. Intensification towards improved fallow systems or plantations is inhibited by poor site conditions, the threat of destruction by elephants, and insecure tenure.